2019
DOI: 10.3390/su11102845
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Runoff Contributing from the Agriculturally Intensive San Joaquin River Watershed to Bay-Delta in California

Abstract: Nitrogen loading from agricultural landscapes can trigger a cascade of detrimental effects on aquatic ecosystems. Recently, the spread of aquatic weed infestations (Eichhornia crassipes, Egeria densa, Ludwigia spp., and Onagraceae) in the Sacramento-San Joaquin Delta of northern California has raised concerns, and nitrogen loading from California’s intensive farming regions is considered as one of the major contributors. In this study, we employed the Soil and Water Assessment Tool (SWAT) to simulate nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…The NSE and KGE results for the original and modified equations were statistically similar, although the Pbias indicated slightly better agreement (6.5% versus 8.0%) for the modified method. These results are similar to those found by Wang et al (2019), where there were no differences between the two methods for comparing streamflow on a monthly basis. The NSE and Pbias values exceeded ratings of very good and good (table 4), respectively, underscoring that the accuracy of the hydrological simulations was maintained with both methods.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The NSE and KGE results for the original and modified equations were statistically similar, although the Pbias indicated slightly better agreement (6.5% versus 8.0%) for the modified method. These results are similar to those found by Wang et al (2019), where there were no differences between the two methods for comparing streamflow on a monthly basis. The NSE and Pbias values exceeded ratings of very good and good (table 4), respectively, underscoring that the accuracy of the hydrological simulations was maintained with both methods.…”
Section: Resultssupporting
confidence: 90%
“…It is important to note that all of these model applications (Kalcic et al, 2015;Boles et al, 2015;Guo et al, 2018) were performed for relatively small watersheds with drainage areas ≤ 69 km 2 (table 1). Wang et al (2019) did not report significant differences between the two methods in monthly flow simulations for a 40,000 km 2 watershed (table 1). However, they found that the modified method resulted in an improved match between simulated and measured nitrate loads.…”
mentioning
confidence: 87%
“…At the pasture site, the soil pH was even lower than at the alfalfa and corn site, with a mean value of 4.8. Therefore, the low nifH gene abundance at the pasture site will show that atmospheric N fixation is negligible, and cattle grazing could be currently the main N input source (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(Miller et al, 2008;Miller and Fujii, 2010). Since intensive agriculture is causing elevated nitrate concentration in both drainage water and river water (Schlegel and Domagalski, 2015;Wang et al, 2019), all of these wetlands will receive N through the inflow water, which maintains the water level. In addition, all of these wetland sites will experience at least some growth of Azolla spp.…”
Section: Site Descriptionmentioning
confidence: 99%